KOMUNIKASI ORGANISASI LAYANAN PERBANKAN MENGGUNAKAN “PRINSIP 46” DALAM MEMPREDIKSI LOYALITAS NASABAH - Pur Astutik (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study aims to analyze organizational communication in banking services based on the “Principle 46” framework in predicting customer loyalty. Principle 46 encompasses the core values of profess ionalism, integrity, customer orientation, and continuous improvement that guide organizational behavior. The study employs a quantitative correlational approach. Data were collected through questionnaires distributed to 61 active customers selected based on specific criteria. Data analysis was conducted using simple linear regression to exam ine the relationship between organizational communication as the independent variable and customer loyalty as the dependent variable. The results indicate that organizational communication based on Princ iple 46 has a positive and significant effect on customer loyalty, contri buting 18.5 to its variance. These findings suggest that customer loyal ty is influenced not only by financial products and service quali ty but also by how effectively organizations communicate and internalize their institutional values. It is recommended that the company the implementation of Principle 46, particularly among frontline employ yees, to create sustainable and competitive service differentiation.